2021
DOI: 10.1111/jcpe.13456
|View full text |Cite|
|
Sign up to set email alerts
|

Economic evaluations in the treatment and evaluation of patients with periodontal disease: A critical review

Abstract: Aim: To evaluate the types and quality of reporting of economic evaluations carried out in the clinical management of periodontal disease over 32 years from 1987 to 2019. Material and methods: A systematic search of articles from 1987 to 2019 was conducted using PubMed, Web of Science, The Cochrane Central Register of Controlled Trials, Health Technology Assessment Database and Embase. The quality of the economic evaluations was assessed based on the Consolidated Health Economic Evaluation Reporting Standard c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
(144 reference statements)
0
7
0
2
Order By: Relevance
“…Our updated review noted there was a diversity of dental and generic health outcomes used in the studies included in this review and identified that there was sparse evidence for cost-effective interventions to prevent periodontitis [29,[114][115][116], which is a consistent finding from previous reviews [23][24][25][26][27][28][29]. Different outcome measures do not allow comparison between interventions or diseases to guide resource allocation.…”
Section: Discussionmentioning
confidence: 84%
“…Our updated review noted there was a diversity of dental and generic health outcomes used in the studies included in this review and identified that there was sparse evidence for cost-effective interventions to prevent periodontitis [29,[114][115][116], which is a consistent finding from previous reviews [23][24][25][26][27][28][29]. Different outcome measures do not allow comparison between interventions or diseases to guide resource allocation.…”
Section: Discussionmentioning
confidence: 84%
“…The societal aspects of treatment were measured in Caries Research, Journal of Clinical Periodontology and the Journal of Oral & Facial Pain and Headache by investigating the cost‐effectiveness of various treatment (McMahon et al., 2020; Shin et al., 2021; Tay et al., 2021; Vos et al., 2018). A detailed list of all included studies from the four journals is available in Appendix S2.…”
Section: Resultsmentioning
confidence: 99%
“…Non-surgical periodontal treatment is associated with mechanical removal of the soft and hard deposits from an exposed root surface in a 'closed' manner in addition to oral hygiene instructions and patient motivation. Different strategies of non-surgical periodontal treatment have been designed to successfully arrest the progression of periodontitis and re-establish a healthy ecosystem [21], frequently having economic implications [22,23]. Treatment improves patient behaviour (i.e.…”
Section: Periodontal Wound Healing and Treatment Considerations Of Pe...mentioning
confidence: 99%